Peran Multitasking Orang Tua Dalam Membimbing Belajar Anak - Prihatin, Metros (Jurnal Ilmiah Mandala Education (JIME), 2022)
This paper is "Qualitative Field Research" (field research). The subject of research is "multitasking parents". With data collection techniques in the form of interviews, observation and documentation. It aims to analyze and describe the multitasking roles of parents in guiding children's learning, including selling merchandise while tidying up shops, tidying clothes while cooking, doing office assignments while working from home, teaching students the Koran which are all done while guiding children's learning. This multitasking role is carried out by parents at this time during learning from home and working from home. Keywords: the role of parents, multi-tasking, and learning